Epidemiological profile of cerebral venous thrombosis in a hospital in Salvador-BA: Proposal for a research project (Research, Society and Development, 2022)
Cerebral venous thrombosis (CVT) is a cerebrovascular disease that, despite being relatively rare, is an important cause of morbidity and mortality when present. Although it is related to a series of risk factors with high prevalence within the world population, such as hypertension, obesity, diabetes mellitus and hypertriglyceridemia, CVT is curable, especially when the diagnosis is established early. Therefore, the objective of this study was to establish a clinical-topographic description of the condition of patients affected by this pathology, in a referral hospital in Neurology in Salvador, Bahia. For this, the construction of a research project model was elaborated, in order to clarify steps for replication by the scientific community, adapted according to the location of the researchers. Among the results presented, there is the proposal of an observational, retrospective and descriptive method, with the purpose of instituting a clinical-topographic study about the symptomatological picture of patients with CVT in a hospital in Salvador, Bahia. It is concluded that CVT is a relevant cause of the increase in morbidity and mortality rates in the current environment, although it has a low incidence. Consequently, this study has significant importance, as it establishes a research project referring to the descriptive analysis of patients affected by CVT, in order to be replicated by the scientific community.